Education for sustainability: a reconstruction of political subjectivities in the era of climate change - Yeremieieva, Irina; Margulov, Artur; Chebakova, Yuliia; Holovii, Liudmyla; Pyurko, Vladyslav (Interacción y Perspectiva, 2025)
A priori, it is evident that the interaction between sustainability, political subjectivities and ecocentric ethics is neither simple nor free of conflicts; rather, it is marked by a series of productive tensions that highlight the complexities inherent to any change of socioecological mentality in the 21st century. Against this backdrop, the objective of this research is to critically reflect on how the political subjectivities of world leaders such as (Donald Trump and Emmanuel Macron), represent climate change and, simultaneously, to explore the potential of education for sustainability in the transformation of collective imaginaries and power elites. Through a hermeneutic methodology based on a mayeutic exercise, the interpretation of the sources consulted allows us to conclude that education for sustainability is presented as an ethical and, simultaneously, political commitment to life, capable of articulating resistance to ecological devastation and the creation of viable alternatives for the common future. It is not enough to reform curricular content; it is now necessary to transform the practices, links and structures that perpetuate speciesist inequality and environmental destruction.